On the analysis of impedance-driven reverse flow dynamics - Lee, Vincent; Chai, C.; Law, M.; Wee, S. (School of engineering, Taylor's University College, 2017)
Impedance pump is a simple valve-less pumping mechanism, where an elastic tube is joined to a more rigid tube, at both ends. By inducing a periodic asymmetrical compression on the elastic tube will produce a unidirectional flow within the system. This pumping concept offers a low energy, low noise alternative, which makes it an effective driving mechanism, especially for micro-fluidic systems. In addition, the wave-based mechanism through which pumping occurs infers many benefits in terms of simplicity of design and manufacturing. Adjustment of simple parameters such as the excitation frequencies or compression locations will reverse the direction of flow, providing a very versatile range of flow outputs. This paper describes the experimental analysis of such impedance-driven flow with emphasis on the dynamical study of the reverse flow in open-loop environment. In this study, tapered section with converging steps is introduced at both ends of the elastic tube to amplify the magnitude of reverse flow. Study conducted shows that the reverse peak flow is rather significant with estimate of 23% lower than the forward peak flow. The flow dynamics on the other hand has shown to exhibit different characteristics as per the forward peak flow. The flow characteristics is then studied and showed that the tapered sections altered the impedance within the system and hence induce a higher flow in the reverse direction.